CEH v9 Certified ethical hacker version 9 : study guide - Oriyano, Sean-Philip (Sybex, 2016)
The ultimate preparation guide for the unique CEH exam. The CEH v9: Certified Ethical Hacker Version 9 Study Guide is your ideal companion for CEH v9 exam preparation. This comprehensive, in-depth review of CEH certification requirements is designed to help you internalize critical information using concise, to-the-point explanations and an easy-to-follow approach to the material. Covering all sections of the exam, the discussion highlights essential topics like intrusion detection, DDoS attacks, buffer overflows, and malware creation in detail, and puts the concepts into the context of real-world scenarios. Each chapter is mapped to the corresponding exam objective for easy reference, and the Exam Essentials feature helps you identify areas in need of further study. You also get access to online study tools including chapter review questions, full-length practice exams, hundreds of electronic flashcards, and a glossary of key terms to help you ensure full mastery of the exam material. The Certified Ethical Hacker is one-of-a-kind in the cybersecurity sphere, allowing you to delve into the mind of a hacker for a unique perspective into penetration testing. This guide is your ideal exam preparation resource, with specific coverage of all CEH objectives and plenty of practice material. -Review all CEH v9 topics systematically -Reinforce critical skills with hands-on exercises -Learn how concepts apply in real-world scenarios -Identify key proficiencies prior to the exam The CEH certification puts you in professional demand, and satisfies the Department of Defense's 8570 Directive for all Information Assurance government positions. Not only is it a highly-regarded credential, but it's also an expensive exam-making the stakes even higher on exam day. The CEH v9: Certified Ethical Hacker Version 9 Study Guide gives you the intense preparation you need to pass with flying colors.